Models of optimization of successive systems on the criterion of security against the risk of failures - Капишон, Б. Г.; Корнійчук, М. Т.; Совтус, І. К.; Тетерятник, В. Д. (Proceedings of National Aviation University (archive), 2002)
The method of optimization of complex, successively connected systems is considered at the design and development stage by the criterion of the cost of ensuring security from the risk of system failures, taking into account risk management for the possibility of reducing it. On the basis of the developed modified method of uncertain factors, a method and models are proposed, which allow minimizing the costs of building a system of a given quality with acceptable levels of risk of failures.